2011
DOI: 10.1088/0268-1242/26/8/085016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of a new approach to the analysis of the quasineutral carrier transport in semiconductors and semiconductor structures

Abstract: According to the recently suggested new approach to the description of the quasineutral transport in semiconductors and semiconductor devices, the current-voltage characteristics of the p + -p-n + and p + -n-n + structures fundamentally differ at large W /L ratios and high current densitiesj (W is the base width of a semiconductor structure, and L is the ambipolar diffusion length). In the p + -p-n + structures, the differential resistance R d must steadily decrease with increasing j at high injection levels f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…The thyristor switch-off was simulated using the 'INVESTIGATION' ('ISSLEDOVANIE') software package [15]. This software has already been used to analyze steady state and transient processes in Si and SiC diodes and thyristors (see, e.g., [10,[16][17][18]). The parameters of the simulated thyristor structure corresponded to those described above.…”
Section: Experimental and Simulation Detailsmentioning
confidence: 99%
“…The thyristor switch-off was simulated using the 'INVESTIGATION' ('ISSLEDOVANIE') software package [15]. This software has already been used to analyze steady state and transient processes in Si and SiC diodes and thyristors (see, e.g., [10,[16][17][18]). The parameters of the simulated thyristor structure corresponded to those described above.…”
Section: Experimental and Simulation Detailsmentioning
confidence: 99%
“…Этот метод облегчает нахождение приближенного решения нелинейного уравнения (1). В соответствии с результатами работ [13,17] уравнение непрерывности в области 1 -области QND переноса -приобретает следующий вид:…”
Section: вольт-амперная характеристика диода шотткиunclassified
“…Решение дрейфового уравнения непрерывности (4) хорошо известно и приведено в классической книге [17]. В нашем случае оно имеет вид…”
Section: вольт-амперная характеристика диода шотткиunclassified
“…8,9 It has been shown that the equation describing the carrier and field distributions along the base becomes markedly different. As a result, static 10 and transient 11 characteristics of the structures are strongly changed.…”
mentioning
confidence: 99%